The Use of Elastic Resistance Bands to Reduce Dynamic Knee Valgus in Squat-Based Movements: A Narrative Review - Davis A Forman; Shahab Alizadeh; Duane C Button; Michael WR Holmes (North American Sports Medicine Institute, 2023)
An elastic band wrapped around the distal thighs has recently been proposed as a method for reducing dynamic knee valgus (medial movement of the knee joint in the frontal/coronal plane) while performing squats. The rationale behind this technique is that, by using an external force to pull the knees into further knee valgus, the band both exaggerates the pre-existing movement and provides additional local proprioceptive input, cueing individuals to adjust their knee alignment. If these mechanisms are true, then elastic bands might indeed reduce dynamic knee valgus, which could be promising for use in injury prevention as excessive knee valgus may be associated with a greater risk of sustaining an ACL rupture and/or other knee injuries. Due to this possibility, certain athletic populations have already adopted the use of elastic bands for training and/or rehab, despite a limited number of studies showing beneficial findings. The purpose of this narrative review is to examine current literature that has assessed lower limb muscle activity and/or lower limb kinematics performance on squat-based movements with or without an elastic band(s). Importantly, this paper will also discuss the key limitations that exist in this area, propose suggestions for future research directions, and provide recommendations for training implementations. # Level of Evidence 5